PENGARUH MICRO-INFLUENCER VS VIRTUAL INFLUENCER (AI): ANALISIS PERBANDINGAN TINGKAT KEPERCAYAAN DAN LOYALITAS KONSUMEN MILENIAL DI KOTA BANJARMASIN - Sucidha, Irma; Yuliani, Yuliani (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze and compare the impact of micro-influencers and virtual influencers on consumer trust and loyalty among the millennial generation in Banjarmasin. Amidst the digital marketing transformation, the effectiveness of human figures versus AI-based characters remains a significant subject of debate. Utilizing a quantitative, causal-comparative research design, this study surveyed 125 respondents to evaluate how these two influencer categories shape consumer behavior. Multiple linear regression analysis reveals that micro-influencers exert a more dominant and significant influence on both consumer trust (0.452) and loyalty (0.385) compared to virtual influencers (0.214 and 0.152, respectively). These findings underscore that the